Application of Teledermoscopy in the Diagnosis of Pigmented Lesions - C. B. Barcaui; P. M. O. Lima (International Journal of Telemedicine and Applications)
Background. Dermatology, due to the peculiar characteristic of visual diagnosis, is suitable for the application of modern telemedicine techniques, such as mobile teledermoscopy. Objectives. To evaluate the feasibility and reliability of the technique for the diagnosis of pigmented lesions. Methods. Through the storage and routing method, 41 pigmented lesions were analyzed. After the selection of the lesions during the outpatient visit, the clinical and dermatoscopic images were obtained by the resident physician through the cellphone camera and sent to the assistant dermatologist by means of an application for exchange of messages between mobile platforms. Firstly, the assistant dermatologist described the visualized dermatoscopic structures and defined its diagnosis and conduct, based solely on the evaluation of the clinical and dermatoscopic images, without having the knowledge of the anamnesis data. Afterwards, the same assistant dermatologist evaluated the patient face to face, defining the dermatoscopic structures, diagnosis, and conduct. The data obtained through teledermoscopy and face-to-face assessments were compared and accuracy was defined as the concordance between the diagnoses. Results. A match rate of 90% between teledermoscopic and face-to-face diagnosis was demonstrated (McNemar’s statistical analysis, whose p value was 0.1366, showed no evidence to support the inferiority of the teledermoscopic method).